PERBANDINGAN PRESTASI BELAJAR MATEMATIKA SISWA DENGAN PENDEKATAN CTL ANTARA MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DAN NHT PADA POKOK BAHASAN SISTEM PERSAMAAN LINIER DUA VARIABEL DITINJAU DARI KEPERCAYAAN DIRI SISWA KELAS VIII SMP NEGERI DI KABUPATEN MAD - Susanti, Vera Dewi; Budiyono, Budiyono; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2013)
Abstract: The objectives of research are to find out, in mathematics learning for two-variable linear equation system subject matter: (1) which one providing better achievement, the CTL learning model with STAD, that with NHT or the direct learning model, (2) which one providing better achievement, high, medium or low self-confidence, and (3) in high, medium or low self-confidence, which one providing better achievement, CTL approach with STAD or NHT type or direct learning model.The population of research was the students of Junior High Schools throughout Madiun Regency in the first semester of VIII grade in the school year of 2011/2012. The sampling technique used was stratified cluster random sampling with the students of SMP Negeri 2 Dolopo, SMP Negeri 2 Kebonsari and SMP Negeri 2 Geger as the sample. The instruments used to collect the data included test to obtain the data of mathematic learning achievement and questionnaire for the on of student’s self-confidence. Technique of analyzing data used was 3x3 two-way variance analysis. From the result of analysis, it could be concluded that: (1) The mathematics learning achievement of students using STAD type of cooperative learning model with CTL approach was better than that using NHT type, that using STAD type with CTL approach was better than that using direct learning model, and that using NHT type with CTL approach was better than that using direct learning model. (2) The mathematics learning achievement with high self-confidence was better than that with medium one; that with high self-confidence was better than that with low one; and that with medium self-confidence was better than that with low one. (3) Viewed from self-confidence level, the mathematics learning achievement of the students using STAD type of cooperative learning with CTL approach was better than that using NHT type, that using STAD type of cooperative learning with CTL approach was better than that using direct learning model, and that using NHT type of cooperative learning with CTL approach was better than that using direct learning model.Keywords: Learning model, CTL approach STAD, NHT, , direct learning, self confidence.